Comparative analysis of single-wythe, non-composite double-wythe, and composite double-wythe tilt-up panels - Sandoval, Robee Ybañez (Kansas State University, 2017)
Insulated precast concrete sandwich panels are commonly used for exterior cladding on a building. In recent years, insulated tilt-up concrete sandwich panels are being used for the exterior load-bearing walls on a building. The insulation is sandwiched between exterior and interior concrete layers to reduce the heating and cooling costs for the structure. The panels can be designed as composite, partially composite, or non-composite. The shear ties are used to achieve these varying degrees of composite action between the concrete layers. A parametric study analyzing the standard, solid single-wythe tilt-up concrete wall panel and solid sandwich (double-wythe separated by rigid insulation) tilt-up concrete wall panels subjected to eccentric axial loads and out-of-plane seismic loads is presented. The sandwich tilt-up panel is divided into two categories – non-composite and composite wall panels. The height and width of the different types of tilt-up wall panel is 23 feet (21 feet plus 2-foot parapet) and 16 feet, respectively. The solid standard panel (non-sandwich) is 5.5 inches in thickness; the non-composite sandwich panel is composed of 3.5-inch architectural wythe, 2.5-inch rigid insulation, and 5.5-inch interior load bearing concrete wythe; and the composite sandwich panel is composed of 3.5-inch exterior, load bearing concrete wythe, 2.5-inch insulation, and 5.5-inch interior, load bearing concrete wythe. The procedure used to design the tilt-up wall panels is the Alternative Method for Out-of-Plane Slender Wall Analysis per Section 11.8 of ACI 318-14 Building Code Requirements for Structural Concrete and Commentary. The results indicated that for the given panels, the applied ultimate moment and design moment strength is the greatest for the composite sandwich tilt-up concrete panel. The standard tilt-up concrete panel exhibits the greatest service load deflection. The non-composite sandwich tilt-up concrete panel induced the greatest vertical stress. Additionally, the additional requirements regarding forming materials, casting, and crane capacity is covered in this report. Lastly, the energy efficiency due to the heat loss and heat gain of sandwich panels is briefly discussed in this report. The sandwich tilt-up panels exhibit greater energy efficiency than standard tilt-up panels with or without insulation.
Keywords: Sandwich panel; Non-composite; CompositeTilt-up wall